Pulmonary vein pulsatility in fetuses of diabetic mothers: prenatal Doppler echocardiographic study - Zielinsky,Paulo (2003)
OBJECTIVE: To verify the hypothesis that the pulmonary vein pulsatility index is higher in fetuses of diabetic mothers than it is in normal fetuses of nondiabetic mothers. METHODS: Twenty-four fetuses of mothers with either gestational or previous diabetes (cases), and 25 normal fetuses of mothers without systemic disease (control) were examined. Fetuses were examined through prenatal Doppler and color flow mapping. The pulmonary vein pulsatility index was obtained by placing the pulsed Doppler sample volume over the right superior pulmonary vein and applying the formula (systolic velocity - presystolic velocity)/mean velocity. RESULTS: The mean gestational age of the study fetuses was 30.3±2.7 weeks, and gestational age of the controls was 29±3.3 weeks, with no significant difference in gestational age between groups (p=0.14). Fetuses of diabetic mothers had a mean pulmonary vein pulsatility index of 1.6±1, and those of the control group had an index of 0.86±0.27. CONCLUSION: Fetuses of diabetic mothers had pulmonary vein pulsatility indexes (parameter easily obtained through Doppler echocardiography that may be related to fetal diastolic function) higher than those in fetuses of mothers with normal glycemia.